Taste evaluation of a novel midazolam tablet for pediatric patients: In vitro drug dissolution, in vivo animal taste aversion and clinical taste perception profiles - Cheung, Laurence; Nguyen, M.; Tang, E.; von Ungern Sternberg, B.; Salman, S.; Tuleu, C.; Mohamed Ahmed, A.; Soto, J.; Lim, L. (Elsevier BV, 2018)
© 2017 Elsevier B.V. Harmonized methodologies are urgently required for the taste evaluation of novel pediatric medicines. This study utilized in vitro, in vivo and clinical data to evaluate the palatability of a novel midazolam chocolate tablet. In vitro dissolution experiments showed the crushed tablet to release within 5 min 1.68 mg of midazolam into simulated saliva. This translated to a drug level of 0.84 mg/ml in the oral cavity, which would be higher than the midazolam bitterness detection threshold concentration of 0.03 mg/ml determined in a rat ‘brief access taste aversion’ (BATA) model. The visual analogue scale scores of patients aged 4–16 years prescribed with midazolam pre-surgery showed a clear preference for the midazolam chocolate tablets (3.35 ± 1.04, n = 20) compared to the control midazolam solution (1.47 ± 0.62, n = 17). The clinical data was in agreement with the in vivo rodent data in showing the novel chocolate tablet matrix to be effective at taste-masking the bitter midazolam.